Effect of Storage Condition on Sensory and Microbial Characteristics of Aerobically Packaged Low Fat Milk Nuggets Prepared With Skim Milk Coagulum and Finger Millet Flour - Shahi, Jyanendr Kumar; Roy, Snjeev Kumar; Chauhan, Geeta; Kumar, Pankaj; KUMAR, RAKESH; Behera, Sujit Kumar (Indian Journal of Dairy Science, 2017)
The present study was carried out to determine the physico-chemical, microbiological, sensory properties and storage stability of developed low fat milk nuggets. Two groups of low fat milk nuggets were prepared. First group known as control having skim milk coagulum, refined wheat flour, spices and condiments as ingredients in its formulation while other group known as treatment group additionally contained optimum level of finger millet flour. Developed products were aerobically packaged in low density polyethylene bag and kept under refrigeration (4Â±1â°C). Storage stability of product was evaluated on 0, 3rd ,6th , 9th Â and Â 12th day of storage for physico-chemical, microbiological and sensory parameters. pH value of both groups tended to decrease significantly (p<0.01) over the storage period and pH value of treatment group was significantly (p<0.01) lower than that of control group over the storage period. TBARS values of both the groups increased significantly (p<0.01) with advancement of storage period. Total plate count, psychrophillc and yeast and mold counts of both the groups increased significantly (p<0.01) with the advancement of storage period. Overall acceptability of low fat milk nuggets of treatment group was comparable to that of control ones on even on 12th day of storage.